Main Approaches to Assessing the Quality of Drug Therapy in Cardiology - S. Yu. Martsevich; N. P. Kutishenko; Yu. V. Lukina; N. A. Komkova; N. A. Dmitrieva; O. A. Drapkina (Столичная издательская компания, 2018)
A competent choice of drug therapy in a specific clinical situation is a difficult and important task that a practical doctor must regularly solve in everyday practice, and the consequences of errors in this decision can be quite serious. Therefore, evaluation of the quality of the prescribed therapy is extremely important.In the treatment of cardiovascular diseases, medicines that have a proven effect on the outcomes of the disease, primarily on mortality rates (so-called "life-saving drugs") acquire special significance. There are several classes of such drugs, and in different situations, their positive impact on the prognosis of the disease may be different. On the other hand, one should remember the so-called "drug-related problems" (DRP), which include contraindications to the prescription of certain drugs in a particular patient, the possibility of developing side effects of drug therapy, aggravated by polypharmacy, inter-drug interaction, improper dosage of drugs, etc.In this publication, an attempt is made to identify the main components by which the quality of the prescribed therapy can be evaluated in the treatment of cardiovascular diseases: compliance of prescriptions with official instructions for preparations, modern clinical guidelines, adequate selection of a specific drug within the class, drug formulation, salt of the drug, evaluation of important safety parameters and efficacy of the prescribed drug. In addition, a review of the methods and scales of the composite evaluation of the quality of drug therapy developed to date has been conducted, as well as attempts to improve them and create new ones that continue to the present day. Nevertheless, none of the currently known methods for assessing the quality of therapy is not universal or devoid of shortcomings.Most likely, a universal method of assessing the quality of the prescribed treatment may not exist. In its most general form, it can be said that treatment should be based on modern evidence-based medicine, which is usually reflected in the clinical guidelines, without contradicting the official instruction on the use of the drug, considering the presence of concomitant diseases, that are often the reasons of contraindications to prescribing those or other medicines.